Answer:
Therefore the required expression is
[tex]5\times (x-y)[/tex]
Where
x = 29
y = 14 - 11
Step-by-step explanation:
Given:
Let denote, "29" by "x" and "(14 - 11 )" by "y"
So the difference is given as
[tex]x-y[/tex]
According to the given condition,
five times the difference of "29" and "(14-11)"
[tex]5\times (29- (14-11))[/tex]
Substituting the variables we get the final Expression as
[tex]5\times (x-y)[/tex]
Where
x = 29
y = 14 - 11
Also you can calculate it by re-substituting i.e,
[tex]5\times (29 -(14-11)=5\times (29-14+11)=5\times 26=130[/tex]
Therefore the required expression is
[tex]5\times (x-y)[/tex]
Where
x = 29
y = 14 - 11